Comparison On Compressive Behaviour Of Aluminium Honeycomb And Titanium Alloy Micro Lattice Blocks - Rafidah, Hasan (Trans Tech Publications, 2011)
The paper discusses the compressive behaviour of two materials, the conventional aluminium honeycomb and the new titanium alloy micro lattice blocks. The new titanium alloy micro lattice structure is being developed as core material candidate in sandwich construction for aerospace application. Experimental tests have been done on the blocks in order to compare its property with the aluminium honeycomb. Compression strength as well as compressive behaviour of both materials are compared and observed. The mechanisms that contributed to the differences in their performance are discussed and this will be used to improve the geometrical and structural design of micro lattice structure in order to achieve properties that are superior or at least comparable with that of aluminium honeycomb.